The Social Representation of Women in Bukittinggi Goverment in the Construction of Collective Conciousness - Tyka Rahman (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This paper aimed to discuss social representation of women in the bureaucratic system. The more modern the society is, the wider the space for women is to access various things, for instance, education, economic resources, and positions in workplace. This study focused on how women's accessibility for the positions relating to decision-making. This accessibility revealed how well women re able to play a role in constructing their social world. This study used Serge Moscovici’s Social Representation theory as the analysis tool. Social Representation is a derived theory from the concept of Collective Consciousness created by Emile Durkheim. Moscovici's Social Representation Theory revealed how individual knowledge system shaped by cultural and religious structures influences in making choices and acting to confront social reality. A qualitative approach was used to determine social representation of women on the bureaucratic system. This study analyzed women’s knowledge system which contested with community norms in order to maintain embeddesness to their collective. The social representation of women was the result of negotiation and contestation of knowledge system and individual consciousness with social norms.Tulisan ini bertujuan untuk membahas representasi sosial perempuan pada sistem birokrasi. Semakin modern masyarakat, semakin luas ruang bagi perempuan untuk mengakses berbagai hal, akses terhadap pendidikan, sumber daya ekonomi, dan posisi di ruang kerja. Studi ini berfokus pada aksesibilitas perempuan pada posisi yang berkaitan dengan pengambilan keputusan. Aksesibilitas ini akan mengungkap seberapa mampu perempuan berperan dalam membangun dunia sosialnya. Penelitian ini menggunakan teori Representasi Sosial, Serge Moscovici untuk alat analisis. Teori Representasi Sosial merupakan teori turunan dari konsep Kesadaran Kolektif Emile Durkheim. Teori Representasi Sosial, Moscovici mengungkap sistem pengetahuan individu dibentuk oleh struktur budaya dan agama, sehingga mempengaruhinya dalam membuat pilihan dan menghadapi realitas sosial. Pendekatan kualitatif digunakan untuk mengetahui representasi sosial perempuan pada sistem birokrasi. Studi ini menganalis sistem pengetahuan perempuan berkontestasi dengan norma masyarakat demi menjaga keterlekatan dengan kolektifnya. Representasi sosial perempuan merupakan hasil negosiasi dan kontestasi sistem pengetahuan dan kesadaran individu (individual consciousness) dengan norma sosial